Wayside School is falling down - Sachar, Louis, 1954-; McCauley, Adam (London Bloomsbury Publishing Plc, 2010)
Features more humorous episodes from the classroom on the thirtieth floor of Wayside School, where students learn to tango, face the cafeteria's dreaded mushroom surprise, and study a hobo during show-and-tell.
Sequel to: Sideways Stories from Wayside School.
Elem. School Library Collection
Elem. School Library Collection, January 2001
3.9
3-6
3-6
Keywords: Humorous stories; Schools -- Fiction; Humorous fiction; School stories